2019
DOI: 10.1002/pd.5575
|View full text |Cite
|
Sign up to set email alerts
|

“The communication and support from the health professional is incredibly important”: A qualitative study exploring the processes and practices that support parental decision‐making about postmortem examination

Abstract: Background Consent rates for postmortem (PM) examination in the perinatal and paediatric setting have dropped significantly in the United Kingdom, the United States, and the Western Europe. We explored the factors that act as facilitators or barriers to consent and identified processes and practices that support parental decision‐making. Methods A qualitative study conducted with bereaved parents, parent advocates, and health care professionals in the United Kingdom. Analysis was conducted on 439 free‐tect co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Some bereaved parents will have clear views regarding their level of acceptance for invasiveness of a standard autopsy; however, a subset will be undecided. ‘Decisional drivers’ [ 48 ] include an open approach by a trusted practitioner, adequate time for deliberation and adopting an individualised approach (both in the required depth and amount of information provided). There is rarely a ‘correct’ answer, and each parent will need to feel supported in their personal patient journey [ 46 ].…”
Section: Stakeholder Perceptions Of the Less Invasive Autopsymentioning
confidence: 99%
“…Some bereaved parents will have clear views regarding their level of acceptance for invasiveness of a standard autopsy; however, a subset will be undecided. ‘Decisional drivers’ [ 48 ] include an open approach by a trusted practitioner, adequate time for deliberation and adopting an individualised approach (both in the required depth and amount of information provided). There is rarely a ‘correct’ answer, and each parent will need to feel supported in their personal patient journey [ 46 ].…”
Section: Stakeholder Perceptions Of the Less Invasive Autopsymentioning
confidence: 99%
“…Lewis et al (30) conducted qualitative analysis on free-text survey responses from bereaved parents as well as interviews with bereaved parents, parent advocates and health professionals, to explore the factors that act as facilitators or barriers to autopsy.…”
Section: Communicationmentioning
confidence: 99%
“…Perinatal post-mortem includes deaths occurring as a result of miscarriage, termination of pregnancy, stillbirth, neonatal and late neonatal death, and infant deaths up to one year. It can play an important role in understanding the cause of death of babies and infants (Downe et al, 2012;Lewis et al, 2019). Medical research continues to show, however, that consent for such post-mortems is decreasing (Lewis et al, 2019;Stock et al, 2010), and that both giving and taking consent remains a difficult topic for both professionals and parents (Heazell et al, 2012).…”
Section: The Sensitive Area Of Perinatal Postmortemmentioning
confidence: 99%
“…It can play an important role in understanding the cause of death of babies and infants (Downe et al, 2012;Lewis et al, 2019). Medical research continues to show, however, that consent for such post-mortems is decreasing (Lewis et al, 2019;Stock et al, 2010), and that both giving and taking consent remains a difficult topic for both professionals and parents (Heazell et al, 2012). Studies have identified a number of reasons as to why parents don't want to consent their baby for postmortem.…”
Section: The Sensitive Area Of Perinatal Postmortemmentioning
confidence: 99%
See 1 more Smart Citation